Perancangan Aplikasi Dashboard Monitoring Untuk Peningkatan Akreditasi Program Studi Institusi Di Politeknik APP Jakarta - Mulyo Diningrat, Mohammad Santosa; Simanjuntak, Daniel; Ardian Setiadi, Rizki Muhammad (Politeknik Indonusa Surakarta, 2022)
The National Accreditation Board for Higher Education (BAN-PT) developed the Study Program Accreditation Instrument (IAPS) 4.0 which is output and outcome oriented. Quality measurement is more focused on process, output and outcome aspects, while previous instruments measured more input aspects. The 9 accreditation criteria include Vision, Mission, Objectives and Strategy, Governance, Governance and Cooperation, Students, Human Resources, Finance, Facilities and Infrastructure, Education, Research, Community Service, and Tridharma Outcomes and Achievements. APP Jakarta Polytechnic is one of the tertiary institutions within the Ministry of Industry of the Republic of Indonesia which is under the Industrial Resource Development Agency (BPSDMI) which aims to realize Good University Governance. In accordance with the Vision of the APP Jakarta Polytechnic, namely